2023
DOI: 10.3389/fmolb.2023.1208132
|View full text |Cite
|
Sign up to set email alerts
|

Integrative analysis of circadian clock with prognostic and immunological biomarker identification in ovarian cancer

Abstract: Objective: To identify circadian clock (CC)-related key genes with clinical significance, providing potential biomarkers and novel insights into the CC of ovarian cancer (OC).Methods: Based on the RNA-seq profiles of OC patients in The Cancer Genome Atlas (TCGA), we explored the dysregulation and prognostic power of 12 reported CC-related genes (CCGs), which were used to generate a circadian clock index (CCI). Weighted gene co-expression network analysis (WGCNA) and protein-protein interaction (PPI) network we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 79 publications
0
1
0
Order By: Relevance
“…ANP32B , a member of ANP32 family proteins, is mainly involved in the regulation of gene transcription, and the knockdown of ANP32B has been observed to facilitate apoptosis and hinder cell proliferation in AML cells [56] . Despite the lack of studies specifically focusing on the relationship between SNRPC and AML, evidence suggests that the product of this ribosome-related gene was involved in mRNA splicing and protein synthesis [57] and served as a tumor suppressor gene in various tumors such as hepatocellular carcinoma [58] and ovarian cancer [59] . In our present study, we identified these three genes that can serve as a novel set of biomarkers for evaluating the therapeutic efficacy of AZA/VEN in treating AML.…”
Section: Discussionmentioning
confidence: 99%
“…ANP32B , a member of ANP32 family proteins, is mainly involved in the regulation of gene transcription, and the knockdown of ANP32B has been observed to facilitate apoptosis and hinder cell proliferation in AML cells [56] . Despite the lack of studies specifically focusing on the relationship between SNRPC and AML, evidence suggests that the product of this ribosome-related gene was involved in mRNA splicing and protein synthesis [57] and served as a tumor suppressor gene in various tumors such as hepatocellular carcinoma [58] and ovarian cancer [59] . In our present study, we identified these three genes that can serve as a novel set of biomarkers for evaluating the therapeutic efficacy of AZA/VEN in treating AML.…”
Section: Discussionmentioning
confidence: 99%